2018
DOI: 10.1002/bjs.10769
|View full text |Cite
|
Sign up to set email alerts
|

Survival following liver transplantation for liver-only colorectal metastases compared with hepatocellular carcinoma

Abstract: The low-risk group of patients with colorectal cancer and unresectable liver-only disease had a 5-year OS rate following liver transplantation similar to that of patients with HCC with lesions within the Milan criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
4
44
0
1
Order By: Relevance
“…22 Similar to the experience seen in liver resection [24][25][26] and palliative chemotherapy, 27 right-sided tumors were associated with an inferior outcome, with no patient surviving 5 years. 22 Similar to the experience seen in liver resection [24][25][26] and palliative chemotherapy, 27 right-sided tumors were associated with an inferior outcome, with no patient surviving 5 years.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…22 Similar to the experience seen in liver resection [24][25][26] and palliative chemotherapy, 27 right-sided tumors were associated with an inferior outcome, with no patient surviving 5 years. 22 Similar to the experience seen in liver resection [24][25][26] and palliative chemotherapy, 27 right-sided tumors were associated with an inferior outcome, with no patient surviving 5 years.…”
Section: Discussionmentioning
confidence: 69%
“…Because recurrence alone is not predictive of short survival, DFS is not an appropriate outcome parameter with which to assess the efficacy of LT in CRLM. 22 Similar to the experience seen in liver resection [24][25][26] and palliative chemotherapy, 27 right-sided tumors were associated with an inferior outcome, with no patient surviving 5 years. Thus, caution is probably warranted in offering these patients LT ( Figure 4B).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…122 Moreover, a retrospective analysis using the SECA-I data was able to select a low-risk population (Oslo score 0-3) with a 5-year OS rate of 75%. 127 Another retrospective analysis on the SECA study data helped identify other predictors of post-transplant OS, such as the 'metabolic tumour volume' and 'the total lesional glycolysis' of the CLRM measured by 18 F-FDG PET/CT, 128 which could have a role in identifying patients with minor extrahepatic disease. 129 The recently published SECA-II trial showed that response to neoadjuvant chemotherapy is, in fact, important.…”
Section: Patient Selection Has To Be Refinedmentioning
confidence: 99%
“…A hard but potentially curative treatment, such as LT, should be offered to (often young) patients, taking into consideration that, so far, the only alternative is the perspective of chronic cancer. Indeed, LT is becoming a game changer in the treatment of other secondary liver malignancies15,16 and LT from living donation is a resourceful approach in transplant oncology. Livingdonor LT often constitutes the treatment of last resort in case of notyet-validated indications, which, in many allocation systems, prevent such patients from being registered on the waiting list.…”
mentioning
confidence: 99%